Why Elections Prompt More Corruption, Clientelism, and Forbearance? A Study of Attitudes in Albania, Kosovo, and North Macedonia - Imami Drini; Polese Abel (Comparative Southeast European Studies)
Corruption is often defined as the abuse of public functions for private gain, but research has expanded this view to include clientelism and forbearance, particularly in neo-patrimonial contexts. While forbearance has been widely studied, it remains largely unexplored in Southeastern Europe, where corruption is often oversimplified. This article innovatively combines forbearance, electoral corruption, and clientelism to analyse tax authorities’ behaviour during election periods in three Western Balkan countries. Findings suggest that due to staff politicisation and various other motives, tax authorities adjust their actions around elections, aligning with forbearance and electoral clientelism. This behaviour fosters tax evasion and market distortions, highlighting the need for a more in-depth investigation into these dynamics in the region.